Revisiting information security risk management challenges: a practice perspective. (3rd June 2019) - Bergström, Erik; Lundgren, Martin; Ericson, Åsa
Abstract : Purpose: The study aims to revisit six previously defined challenges in information security risk management to provide insights into new challenges based on current practices. Design/methodology/approach: The study is based on an empirical study consisting of in-depth interviews with representatives from public sector organisations. The data were analysed by applying a practice-based view, i.e. the lens of knowing (or knowings). The results were validated by an expert panel. Findings: Managerial and organisational concerns that go beyond a technical perspective have been found, which affect the ongoing social build-up of knowledge in everyday information security work.. Research limitations/implications: The study has delimitation as it consists of data from four public sector organisations, i.e. statistical analyses have not been in focus, while implying a better understanding of what and why certain actions are practised in their security work. Practical implications: The new challenges that have been identified offer a refined set of actionable advice to practitioners, which, for example, can support cost-efficient decisions and avoid unnecessary security trade-offs. Originality/value: Information security is increasingly relevant for organisations, yet little is still known about how related risks are handled in practice. Recent studies have indicated a gap between the espoused and the actual actions. Insights from actual, situated enactment of practice can advise on process adaption and suggest more fit approaches.